Comparative Study on Criminal Penalties According to The Perspective of Islamic Criminal Law and The Indonesian Criminal Law Code - Ulum , Miftahul; Nasiri , Nasiri; Repo , Nora (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
The issue of punishment in Islam is by raising one type of punishment that is often not brought to the surface, namely the fine (diyat) as an alternative type of punishment. Sentencing also costs a lot of money, for example in the costs of court proceedings, imprisonment, parole, consultation centers that must be attended, and collection of fines. The method used in this research is a normative juridical comparison between Islamic Law and the Criminal Code (KUHP). The research specification used is descriptive analysis. The data collected and processed to support this research used library research which was processed qualitatively. All of our data is separated by data that is relevant or irrelevant to this research. The results of the research and data analysis in this study state that: first, in Islamic Criminal Law there is no such thing as a complaint offense, all jarimahs, be it hudud, qishos, diyat, and takzir, are all ordinary offenses. Adultery in Islamic law is not a complaint offense, whereas in the Criminal Code Article 284 the crime of adultery is a complaint offense, and is included in the category of absolute complaint offense. Second, in proving adultery in Islamic criminal law, it is proven by four things: testimony, confession, qarinah (indication), and li'an. However, this is not the case with the Criminal Code, because the criminal act of adultery is included in the category of an absolute complaint offense, there must be a complaint beforehand so that the offense can be processed